Variations on the expertise of two attributes of physical soil due to differences in the method of global satellite navigation - Zerbato, Cristiano [UNESP]; Compagnon, Ariel M.; Voltarelli, Murilo A.; Rosalen, David L. [UNESP]; Furlani, Carlos E.A. [UNESP] (My University, 2016)
The mechanical resistance to penetration when related to the water content is an indicator often used of soil compaction, the use of positioning methods for greater accuracy of this review is important. In this context, this study aimed to determine the variability of positioning methods provided by GPS receivers to determine the spatial behavior of physical attributes related to soil compaction. The study area is located in the municipality of Jaboticabal, around the latitude 21°15'22S and longitude 48°18'58W, being characterized with a clayey Oxisol. The variables used as parameters of soil physical properties were the mechanical resistance to penetration and water content, using a sampling grid of 20 x 20 m, totaling 60 points. We used six models of GPS receivers: Garmin Etrex Vista, Garmin Etrex 30, Ashtech MM6, Trimble Nomad, Garmin Map 62 and Trimble R6, with all georeferenced points in the regular grid intersections. The georeferencing using GPS receivers (single point positioning and post-processed differential correction) interfered in characterizing the spatial variability of soil resistance to penetration, differently for some receivers to the water content attribute. Positioning methods with post-processed differential correction, using R6 and MM6 models, better define the management zones of soil resistance to penetration.
Keywords: GPS; Penetrometer; Soil compaction; Soil water content